Socially Desirable Responding and College Students with Dyslexia: Implications for the Assessment of Anxiety and Depression. (26th July 2017) - Nelson, Jason M.; Liebel, Spencer W.
Abstract : We investigated self‐reported depressive and anxiety‐related symptoms among college students with dyslexia, with emphasis on the role of socially desirable responding (SDR) in understanding these reports. Analyses included examination of differences in self‐reported depressive symptoms, anxiety‐related symptoms, and SDR. We also examined the relationships among SDR, depressive symptoms, anxiety‐related symptoms, and reading skills. Participants with dyslexia demonstrated significantly higher SDR than did participants without dyslexia, and higher SDR was significantly associated with lower self‐reported depressive and anxiety‐related symptoms. Moreover, higher SDR was significantly associated with lower reading skills. There was no group difference on anxiety‐related symptoms, but participants with dyslexia had higher depressive symptoms than did participants without dyslexia when SDR was controlled. Implications for the assessment of anxiety and depression among college students with dyslexia are discussed. Copyright © 2017 John Wiley & Sons, Ltd.